2021
DOI: 10.48550/arxiv.2106.02808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Variational Perspective on Diffusion-Based Generative Models and Score Matching

Abstract: Discrete-time diffusion-based generative models and score matching methods have shown promising results in modeling high-dimensional image data. Recently, Song et al. (2021) show that diffusion processes that transform data into noise can be reversed via learning the score function, i.e. the gradient of the logdensity of the perturbed data. They propose to plug the learned score function into an inverse formula to define a generative diffusion process. Despite the empirical success, a theoretical underpinning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Concurrent to our work, Song et al [2021a], Huang et al [2021], and Vahdat et al [2021] also derived variational lower bounds to the data likelihood under a continuous-time diffusion model. Where we consider the infinitely deep limit of a standard VAE, Song et al [2021a] and Vahdat et al [2021] present different derivations based on stochastic differential equations.…”
Section: Related Worksupporting
confidence: 65%
See 1 more Smart Citation
“…Concurrent to our work, Song et al [2021a], Huang et al [2021], and Vahdat et al [2021] also derived variational lower bounds to the data likelihood under a continuous-time diffusion model. Where we consider the infinitely deep limit of a standard VAE, Song et al [2021a] and Vahdat et al [2021] present different derivations based on stochastic differential equations.…”
Section: Related Worksupporting
confidence: 65%
“…Where we consider the infinitely deep limit of a standard VAE, Song et al [2021a] and Vahdat et al [2021] present different derivations based on stochastic differential equations. Huang et al [2021] considers both perspectives and discusses the similarities between the two approaches. An advantage of our analysis compared to these other works is that we present an intuitive expression of the VLB in terms of the signal-to-noise ratio of the diffused data, which then leads to new results on the invariance of the generative model and its VLB to the specification of the diffusion process.…”
Section: Related Workmentioning
confidence: 99%
“…Diffusion models are capable of generating high-quality images that can compete and even outperform the latest GAN methods [10,16,33,40]. A variational framework for the likelihood estimation of diffusion models is introduced by Huang et al [19]. Subsequently, Kingma et al [21] proposed a Variational Diffusion Model that produces state-of-the-art results in likelihood estimation for image density.…”
Section: Related Workmentioning
confidence: 99%
“…In practice, the choice of λ(t) can largely affect the performance of SGM. Fortunately, recent works (Song et al, 2021;Huang et al, 2021) have shown that the log-likelihood of SGM, despite being complex, can be parameterized as follows:…”
Section: Score-based Generative Model (Sgm)mentioning
confidence: 99%
“…The underlying relation between the optimization principle of SB and modern generative training, in particular SGM, remains relatively unexplored, despite their intimately related problem formulations. More importantly, with the recent connection between SGM and log-likelihood estimation (Song et al, 2021;Huang et al, 2021), it is crucial to explore whether there exists an alternative way of training SB that better respects, or perhaps generalizes, modern training of SGM, so as to solidify the suitability of SB as a principled generative model.…”
Section: Introductionmentioning
confidence: 99%